2005
DOI: 10.1111/j.1748-5827.2005.tb00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of dermoid sinus in the Rhodesian ridgeback

Abstract: Bias in heredity pattern may be caused by undetected dermoid sinus type V. Improved clinical diagnosis of all dermoid sinus types is therefore crucial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…However, some authors recently proposed that a distinction should be made in dogs and cats, as it is done in humans, between dermoid cysts and DSes based on the presence in the latter of a connection to the skin [4,27,56,57]. Similarly, other authors identified different types of DS in dogs and considered dermoid cyst as a specific type of DS lacking an opening on the skin [19,26,35,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some authors recently proposed that a distinction should be made in dogs and cats, as it is done in humans, between dermoid cysts and DSes based on the presence in the latter of a connection to the skin [4,27,56,57]. Similarly, other authors identified different types of DS in dogs and considered dermoid cyst as a specific type of DS lacking an opening on the skin [19,26,35,55].…”
Section: Discussionmentioning
confidence: 99%
“…Later, two other types of DS, type V [16] and type VI [32], were introduced. Type V was described as a true dermoid cyst consisting of a closed epithelial-lined sac difficult to detect via palpation of the skin [57]. This can be considered a more accurate use of the term ‘dermoid cyst’ since fistulous tract formation or connection to the epidermis is absent.…”
Section: Discussionmentioning
confidence: 99%
“…[11] The dorsal hair ridge in Rhodesian and Thai Ridgeback dogs is caused by a dominant mutation that also predisposes to the congenital developmental disorder dermoid sinus. The causative mutation is a 133-kb duplication involving three fibroblast growth factor (FGF) genes.…”
Section: Breed Historymentioning
confidence: 99%
“…FGFs play a crucial role in development, suggesting that the ridge and dermoid sinus are caused by dysregulation of one or more of the three FGF genes during development. [11] An important sign to recognize a true Phu Quoc dog is the sword shaped ridge on its back, together with short, thin hair. When facing competitors or running after prey, the hair on their back becomes erect, creating a ridge making the dog look brave and strong.…”
Section: Breed Historymentioning
confidence: 99%
“…spina bifida, spinous process malformations, hemivertebrae, and block vertebrae) may be associated with congenital intracranial or spinal dermoid sinus [6,12,14-18]. Vertebral anomalies associated with limbs malformations are rare in small animals [19,20].…”
Section: Introductionmentioning
confidence: 99%